1991
DOI: 10.1002/sia.740170718
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion between plasma‐treated cellulosic materials and polyethylene

Abstract: Filter paper and greaseproof paper have been exposed to hydrogen or oxygen plasma. The paper surface c o m p ition was determined by ESCA measurements. The unmodified and modified papers then were laminated with polyethylene and the adhesive strength was measured. The hydrogen plasma treatment reduces the cellulose surface and forms low-molecular-weight degradation products. It is shown that the reduction of the ceUulose surface has no influence on the adhesion, but the degradation products strongly decrease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Theoretical O/C values have been reported for cellulose, 0.83, , milled wood lignin, 0.34, ,, and organosolv lignin, 0.26 . With respect to the concentration of C–C groups, theoretically pure cellulose does not have a C–C signal due to structure of the polysaccharide, although there is always a small contribution that is attributed to sample contamination; , however, milled wood and organosolv lignins have a C–C contribution equivalent to 49% , and 55%, respectively. Correlating the two independent approaches in lignocellulose samples yields more reliable data than using either of them alone, as indicated by Johansson et al In Figure the changes in both values after deacetylation and desilylation of TMSC/LAc films are clearly observed: a decrease in the O/C ratio and an increase in the C–C % both follow the increase of the lignin fraction in the blends.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical O/C values have been reported for cellulose, 0.83, , milled wood lignin, 0.34, ,, and organosolv lignin, 0.26 . With respect to the concentration of C–C groups, theoretically pure cellulose does not have a C–C signal due to structure of the polysaccharide, although there is always a small contribution that is attributed to sample contamination; , however, milled wood and organosolv lignins have a C–C contribution equivalent to 49% , and 55%, respectively. Correlating the two independent approaches in lignocellulose samples yields more reliable data than using either of them alone, as indicated by Johansson et al In Figure the changes in both values after deacetylation and desilylation of TMSC/LAc films are clearly observed: a decrease in the O/C ratio and an increase in the C–C % both follow the increase of the lignin fraction in the blends.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the concentration of C–C groups, pure cellulose does not have a C–C signal theoretically. However, there is always a small contribution because of sample contamination . The C–C contributions of milled wood and organosolv lignin are 49 and 55%, respectively. , Correlating the O/C value and the concentration of C–C groups in lignocellulose samples can get more reliable data .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that cold plasma environments are suitable for tailoring surface characteristics of cellulosic substrates and for increasing adhesion with their synthetic counterparts. [61][62][63] However, surface treatments of thermoplastics were also found to be effective in creating composites. 64 Results from hydrogen and oxygen RF-plasma treatments of fi lter paper (open texture and free from low-molecular-weight materials) and grease-proof paper (closed texture and the presence of lowmolecular-weight compounds) indicated that hydrogen plasma environments reduce the cellulose surfaces and generate low molecular weight degradation products, whereas oxygen plasma exposure increases the relative surface oxygen content and improves adhesion (see Figure 10).…”
Section: Plasma Surface Modifi Cation In Cellulosic Fi Bre-based Compmentioning
confidence: 97%
“…64 Results from hydrogen and oxygen RF-plasma treatments of fi lter paper (open texture and free from low-molecular-weight materials) and grease-proof paper (closed texture and the presence of lowmolecular-weight compounds) indicated that hydrogen plasma environments reduce the cellulose surfaces and generate low molecular weight degradation products, whereas oxygen plasma exposure increases the relative surface oxygen content and improves adhesion (see Figure 10). 61 It was shown that reduction of cellulose surfaces does not infl uence the adhesion signifi cantly. However, the presence of degradation products strongly diminishes this characteristic.…”
Section: Plasma Surface Modifi Cation In Cellulosic Fi Bre-based Compmentioning
confidence: 99%